2005
DOI: 10.1080/02678290500033950
|View full text |Cite
|
Sign up to set email alerts
|

Computational modelling of light propagation in textured liquid crystals based on the finite‐difference time‐domain (FDTD) method

Abstract: Light propagation through uniaxial rod-like nematic liquid crystal films containing singular (thin) and non-singular (thick) line disclinations is computed using the finite-difference timedomain method (FDTD), which is based on accurate numerical solutions to the governing Maxwell equations. The results obtained by the FDTD method are compared with classical matrix-type methods, including the aggregate model and Berreman's method. It is found that the optical signals for singular and non-singular defects predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The FDTD method accommodate multidimensional inhomogeneity of the dielectric tensor, it is capable of directing spherical waves, plane waves or Gaussian beams while in arbitrary incidence on material. Now it is well developed to study the light propagation in isotropic and anisotropic media and its efficiency has been proved in various light-LC problems [16][17][18]. This consolidates us in the choice of such a tool.…”
Section: Model Descriptionmentioning
confidence: 93%
“…The FDTD method accommodate multidimensional inhomogeneity of the dielectric tensor, it is capable of directing spherical waves, plane waves or Gaussian beams while in arbitrary incidence on material. Now it is well developed to study the light propagation in isotropic and anisotropic media and its efficiency has been proved in various light-LC problems [16][17][18]. This consolidates us in the choice of such a tool.…”
Section: Model Descriptionmentioning
confidence: 93%
“…The finite-difference time-domain (FDTD) computation [1][2][3] of Maxwell's equations has been widely used as an efficient simulation tool to successfully predict lightwave propagation within liquid crystal (LC) devices [4][5][6][7][8][9]. Here, the FDTD method can simulate the complex anisotropic LCs by considering strong scattering and diffractive effects due to the rapid LC variation as well as spatial inhomogeneties of the LC director orientation, while the commonly used matrix methods are limited by specific types of geometries in modeling anisotropic structures [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The FDTD method is established as an accurate numerical method to solve Maxwell's equations and as an efficient tool for simulation of light propagation in liquid crystals containing complex textures. 35 It has been shown that the FDTD method is capable of predicting optical responses to textured nematic liquid crystal films containing non-uniform orientation induced by variations in surface anchoring. 36 The interaction between the incident light and the nanoscale periodic structure shows bistructural color reflection through hydration and dehydration.…”
Section: Introductionmentioning
confidence: 99%